ACTIVE CITIZENSHIP: PARTICIPATION OF VILLAGE COMMUNITIES IN VILLAGE SOCIAL PARTICIPATION PRACTICES AND VILLAGE TRANSFORMATION TOWARDS THE CITY - MUHAMMAD FADLI (P3M Stia Al Gazali Barru and Meraja media, 2019)
[Full Paper] to pdf Copyright (c) 2018 Meraja journal